Evaluating E-Administration Features on User Satisfaction Using the Kano Model: A Melung Village-Owned Enterprise Case Study - Albana, Ilham; Ihsan, Imamul; Firnandri, Yerikho Putra (Journal of Information System and Informatics, 2024)
This research evaluates user satisfaction with the e-administration system at the Village-Owned Enterprises (BUMDes) Melung, focusing on identifying features that influence user satisfaction using the Kano model. A survey was conducted with 50 respondents who are active users of the system, analyzing 16 key features, including user registration, online payment, financial transparency, and service reporting. The results indicate that the Online Payment and Financial Transparency features are categorized as "Must-be," meaning these features are considered very important and must function optimally for users to remain satisfied. Meanwhile, the Tour Package Booking and Service Reporting features fall into the "One-dimensional" category, where improvements in the quality of these features directly correlate with increased user satisfaction. These findings suggest that fundamental features supporting reliability and accessibility are top priorities, while optimizing other features can further enhance overall user satisfaction. Development recommendations include improving performance on critical features to ensure a more responsive and efficient e-administration system.